Two Decades of Legislative Politics and Governance in Nigeria’s National Assembly
XXXI, 394 p. 28 illus., 25 illus. in color.
Keywords: This book unpacks two decades of Nigeria’s National Assembly spanning 4th–8th legislative sessions. It focuses on the core areas of legislative functions – lawmaking, appropriation, oversight and representation – in examining the achievements, challenges and prospects of the legislature. This is particularly important because Nigeria being the most populous country in Africa is a crucial bastion of democratic governance in the region. Therefore, conducting deep diagnostics of the federal legislature as the custodian of popular mandate and the anchor of accountability offered immense opportunity for learning that would catalyze further institutional reforms and democratic consolidation. Fatai Ayinde Aremu is a Professor of Political Science, University of Ilorin, Nigeria.He is presently a Directing Staff at the National Institute for Policy and Strategic Studies (NIPSS), Nigeria’s apex policy think tank. He is the author of Asymmetrical Foreign Policy Behaviour of Japan and China (2011) and co-editor of Introduction to International Relations (2012). Adebola Rafiu Bakare teaches in the Department of Political Science, University of Ilorin, Nigeria. His research interest is on legislative studies, governance institutions, psephology and security studies. He is the founder and Executive Director of Centre for Legislative Research, Documentation and Training (CLRD&T).